2016
DOI: 10.1186/s12903-016-0211-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oral health on health-related quality of life: a cross-sectional study

Abstract: BackgroundDespite the consensus regarding the existence of a relationship between “impacts on oral health” and “health-related quality of life”, this relationship, considering the latent nature of these variables, is still poorly investigated. Thus, we performed this study in order to determine the magnitude of the impacts of oral health, demographic and symptom/clinical variables on the health-related quality of life in a Brazilian sample of dental patients.MethodsA total of 1,007 adult subjects enrolled in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 28 publications
3
83
0
11
Order By: Relevance
“…This is similar to the findings of other studies. 18 It has been demonstrated that there was a significant relationship between self-reported oral health and OHIP-14 prevalence and OHIP-14 sum, so that the participants with good oral health had the lowest scores (improved OHRQoL). Our study indicated that there is a significant association between bleeding gums and OHRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the findings of other studies. 18 It has been demonstrated that there was a significant relationship between self-reported oral health and OHIP-14 prevalence and OHIP-14 sum, so that the participants with good oral health had the lowest scores (improved OHRQoL). Our study indicated that there is a significant association between bleeding gums and OHRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…While bearing in mind the differences in the experimental design, it was also observed that the shift in the OHIP scores was more for the sonic than the control group, with the largest difference in the functional limitation, psychological discomfort and physical disabilities domains. 10,11 TA B L E 4 Changes in biochemical parameters (mean ± SD) over the 8-week experimental period in GCF sampling sites 44 Lastly, the duration of toothbrushing is an important determinant of plaque removal. 37 Interestingly, in the treatment of gingivitis and periodontitis, less invasive supragingival procedures had a greater impact on oral health-related quality of life then subgingival procedures.…”
Section: Manual Brush (N = 16)mentioning
confidence: 99%
“…Oral health problem influences eating, talking and other psychosocial areas of life, 1) and it significantly diminishes the quality of life. 2) Certain medical conditions such as diabetes and HIV infection 3) and psychosocial factors such as socioeconomic status 4) and stress 5) were found to be risk factors for poor oral health. Adolescence is an important period with regard to establishing a healthy life-style such as frequent toothbrushing and regular exercise.…”
Section: Introductionmentioning
confidence: 99%